New Approach in Nursing Student Club creates a Smoke – Free Thai Society to Sustainability of Tobacco Control - Ruamsook, Tanawat; Chaiyasung, Phatcharaphan; Pungbangkadee, Rudee (Journal of The Royal Thai Army Nurses, 2023)
Nursing Student Club creates a Smoke – Free Thai Society, have roles and responsibilities in operating to control tobacco consumption for people of all age groups. Nursing students are the main leaders in the operation. The purpose is to reduce the health risk factors from smoking and exposure to secondhand smoke in the from organizing various activities that emphasize participation, promotion, and support in reducing and quitting tobacco consumption. The objective of this article is to purpose guidelines for the operation of the Nursing Student Club creates a Smoke – Free Thai Society for nursing institution according to the roles and responsibilities for nursing student to control tobacco consumption in various forms, such as organizing educational activities or the development of media and innovation of assisting smoking cessation, etc. Therefore, it should be promoted and develop the potential for the Nursing Student Club creates a Smoke – Free Thai Society in every educational institution of nursing for health literacy and behavior. And have behavior of assisting smoking cessation including planning the management of Nursing Student Club creates a Smoke – Free Thai Society to build Thai society smoke free from good practice to be a standard and to create a sustainable smoke free Thai society.